Acting the essence : the performer's work on the self - Campo, Giuliano, 1970- (Routledge, 2022)
"Acting the Essence examines the theory, practice and history of the art of the performer from the perspective of its inner nature as work on oneself, within, around and beyond the pedagogy of the actor. Reflecting primarily on the legacy of Jerzy Grotowski, this book is composed of a series of reflections on the Stanislavskian lineage of practitioners and related authors, in an attempt to renovate awareness of the original path traced by the Russian master and to refine certain ambiguities in contemporary training. In a new media age of image and sound, accompanied by a proliferation of new technologies and means to communicate, emphasised by the COVID-19 crisis, a classical question comes to interrogate us again: what is the essence and the principal objective of the work of the performer? Is performing art still necessary? While proposing a theoretical advancement of the discipline and an historical overview of the relevant practices, this book provides tools for a better understanding of the traditional function of the performer's practice as work on the self, for its ecological renaissance through a conscient use of trance, attention and altered states of consciousness. This book offers insight for students in Drama, Theatre, and Performance courses studying acting and performance at university"--